Towards the goals of the Europe 2020 strategy: Convergence or divergence of the European Union countries? - Agata Szymańska; Elżbieta Zalewska (Comparative Economic Research. Central and Eastern Europe, 2018)
The aim of this article is to investigate the similarities between the EU countries in terms of achieving the Europe 2020 Strategy goals. Due to the latest data availability, the analysis is based on the year 2014. The study uses grouping methods, including the k-means algorithm. The results indicate the existence of a division between the "old" and "new" European Union Member States. However, as is shown, some of the Strategy's targets have already been achieved and some indicators have been nearly achieved, whereas among others, such as implementation of the headline indicator for investment in the R&D sector as a % of GDP is uncertain. The average performance of headline indicators for the EU-15 and EU-13 countries seems to be similar and exhibits the same trend of changes.
Keywords: C10; Q01; 330; Europe 2020 Strategy; cluster analysis; European Union